Tungsten Oxide Nanoparticles as Corrosion Inhibitor of Stainless Steel in Saline Medium - M. Raheem, Haider; A. Salman, Taghried (Al-Nahrain Journal of Science, 2020)
Tungsten oxide (WO3) nanoparticles at various concentrations of 1.7×10-2, 2.5×10-2 and 3.4×10-2 M were electrophoretic deposited onto stainless steel surface for corrosion inhibition investigations with respect to concentration as well as temperature by using potentiostatic polarization technique. Results obtained show that WO3 nano coating was used as a barrier layer for the corrosion protection of stainless steel in saline solution. The morphology of nanoparticles was examined using Scanning Electron Microscopy (SEM).The obtained results indicated that these nanoparticles are good inhibitors. All polarization curves yielded similar behavior pointing to stainless steel corrosion is controlled by the charge transfer process so that the stainless steel dissolution mechanism does not alter due to the presence of the nanoparticles. Generally, increasing the inhibitor concentration and temperatures leads to an increase in the inhibition efficiency. Thermodynamic parameters were calculated, and the energy of activation data obtained of the corrosion reaction was decreased with an increase of the concentration of nanoparticles. It is likely that the adsorption of WO3NP on the surface of stainless steel was chemical in nature.